Tunable Single-Longitudinal-Mode High-Power Fiber Laser - Jonas K. Valiunas; Gautam Das (International Journal of Optics)
We report a novel CW tunable high-power single-longitudinal-mode fiber laser with a linewidth of ∼9 MHz. A tunable fiber Bragg grating provided wavelength selection over a 10 nm range. An all-fiber Fabry-Perot filter was used to increase the longitudinal mode spacing of the laser cavity. An unpumped polarization-maintaining erbium-doped fiber was used inside the cavity to eliminate mode hopping and increase stability. A maximum output power of 300 mW was produced while maintaining single-longitudinal-mode operation.